Latex composition for dip molding, its manufacturing method, and dip molded article manufactured therefrom

JP7660645B2Active Publication Date: 2025-04-11KOREA KUMHO PETROCHEMICAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023185272
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-12-15
Filing Date
2023-10-30
Publication Date
2025-04-11
Estimated Expiration
2043-10-30

AI Technical Summary

Technical Problem

Conventional nitrile-based copolymer latex gloves face challenges in mechanical stability, environmental sustainability, and stickiness issues, leading to reduced durability and increased environmental pollution.

Method used

A method for producing a latex composition for dip molding is developed, involving a monomer mixture of conjugated diene-based, farnesene, ethylenically unsaturated nitrile, and ethylenically unsaturated acid monomers, with additives like emulsifiers and inorganic solvents, and a specific weight ratio of farnesene monomer to total monomers to achieve improved mechanical stability and reduced stickiness.

Benefits of technology

The resulting latex composition and dip molded articles exhibit enhanced mechanical properties such as tensile strength and elongation, improved durability, and reduced stickiness, while being environmentally friendly and renewable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660645000001
    Figure 0007660645000001
  • Figure 0007660645000002
    Figure 0007660645000002
  • Figure 0007660645000003
    Figure 0007660645000003
Patent Text Reader

Abstract

To provide a production method for a latex composition for dip formation that is ecological and excellent in mechanical stability.SOLUTION: A method for producing a latex composition for dip formation includes: (a) preparing a monomer mixture including a conjugated diene-based monomer, a farnesene monomer, an ethylenically unsaturated nitrile monomer, and an ethylenically unsaturated acid monomer; (b) adding an additive including an emulsifier and an inorganic solvent to the monomer mixture; and (c) polymerizing the monomer mixture to produce a copolymer latex, where the ratio of the weight of the farnesene monomer to the total weight of the conjugated diene-based monomer and the farnesene monomer is 5 to 55%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present specification relates to a latex composition for dip molding, a method for producing the same, and a dip-molded article produced therefrom. [Background technology]

[0002] Conventionally, the main raw material of gloves used for medical, agricultural and livestock processing, or industrial purposes has been natural rubber latex. However, when gloves made from natural rubber latex are used, the problem of glove users suffering from contact allergies due to the proteins contained in the natural rubber latex has frequently occurred. Therefore, attempts have been made to manufacture gloves using synthetic rubber latex that does not contain proteins, such as nitrile copolymer latex. Nitrile copolymer latex gloves have superior mechanical strength compared to natural rubber latex gloves, and the demand for them is increasing in the medical and food fields where contact with sharp objects occurs frequently.

[0003] However, conventional nitrile copolymer latex gloves are difficult to decompose naturally after use, and their waste disposal causes serious environmental pollution problems. Therefore, there is an increasing social demand for the development of nitrile copolymer latex gloves that use environmentally friendly and renewable materials and that meet the mechanical properties such as tensile strength and elongation and durability required for latex gloves.

[0004] In addition, conventional nitrile copolymer latex gloves have problems in that the inner surfaces of the gloves stick to each other or become sticky when the hand is put into the gloves, and when powder is treated in a post-treatment process to improve this, problems occur in that the powder adheres to the hand when the glove is worn or causes contamination in the operating room, etc. Therefore, there is a need to develop a nitrile copolymer latex glove that has excellent mechanical properties and durability while improving stickiness inside the glove. Summary of the Invention [Problem to be solved by the invention]

[0005] The present specification is intended to solve the problems of the prior art described above, and one object of the present specification is to provide a method for producing a dip molding latex composition which is environmentally friendly and has excellent mechanical stability.

[0006] Another object of the present invention is to provide a latex composition for dip molding, which has excellent mechanical properties such as tensile strength and elongation, and durability, while being improved in stickiness, and a dip-molded product produced therefrom. [Means for solving the problem]

[0007] According to one embodiment, there is provided a method for producing a latex composition for dip molding, comprising: (a) preparing a monomer mixture including a conjugated diene monomer, a farnesene monomer, an ethylenically unsaturated nitrile monomer, and an ethylenically unsaturated acid monomer; (b) adding an additive including an emulsifier and an inorganic solvent to the monomer mixture; and (c) polymerizing the monomer mixture to produce a copolymer latex, wherein a weight ratio of the farnesene monomer to a total weight of the conjugated diene monomer and the farnesene monomer is 5 to 55%.

[0008] In one embodiment, the conjugated diene monomer may be one selected from the group consisting of 1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, isoprene, and a combination of two or more thereof.

[0009] In one embodiment, the farnesene monomers may be α-farnesene monomers, β-farnesene monomers, or a combination thereof.

[0010] In one embodiment, the ethylenically unsaturated nitrile monomer may be one selected from the group consisting of acrylonitrile, methacrylonitrile, fumaronitrile, α-chloroacrylonitrile, α-cyanoethylacrylonitrile, and combinations of two or more thereof.

[0011] In one embodiment, the ethylenically unsaturated acid monomer may be one selected from the group consisting of methacrylic acid, acrylic acid, itaconic acid, maleic acid, fumaric acid, maleic anhydride, citraconic anhydride, styrenesulfonic acid, monobutyl fumarate, monobutyl maleate, mono-2-hydroxypropyl maleate, and combinations of two or more thereof.

[0012] In one embodiment, the additive may further include a molecular weight regulator.

[0013] In one embodiment, the molecular weight regulator may be one selected from the group consisting of α-methylstyrene dimer, mercaptans such as t-dodecyl mercaptan, n-dodecyl mercaptan, octyl mercaptan, etc., halogenated hydrocarbons such as carbon tetrachloride, methylene chloride, methylene bromide, etc., sulfur-containing compounds such as tetraethylthiuram disulfide, dipentamethylenethiuram disulfide, diisopropylxanthogen disulfide, etc., and combinations of two or more thereof.

[0014] In an embodiment, the content of the molecular weight regulator may be 0.2 to 0.65 parts by weight based on 100 parts by weight of the monomer mixture.

[0015] In an embodiment, the gel content of the copolymer latex prepared in step (c) may be 80% or less.

[0016] According to another embodiment, there is provided a dip molding latex composition produced by the above-mentioned production method.

[0017] According to still another embodiment, there is provided a dip-molded product produced by dip molding the above-mentioned latex composition for dip molding.

[0018] In one embodiment, the dip-formed product may be one selected from the group consisting of medical gloves, agricultural and livestock product processing gloves, and industrial gloves. Effect of the Invention

[0019] The method for producing a dip molding latex composition according to one embodiment of the present specification can be applied to the production of a dip molding latex composition that contains a farnesene monomer and is environmentally friendly and has excellent mechanical stability.

[0020] Furthermore, the latex composition according to another embodiment of the present specification and the dip molded article produced therefrom have excellent mechanical properties such as tensile strength, elongation, etc., and durability, while being improved in stickiness, and can be applied to production of medical gloves, gloves for processing agricultural and livestock products, industrial gloves, etc.

[0021] The effects of one embodiment of this specification should not be limited to the effects described above, but should be understood to include all effects that can be inferred from the configurations described in the detailed description and claims of this specification. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Hereinafter, an embodiment of the present specification will be described with reference to the accompanying drawings. However, the description of the present specification may be embodied in various different forms, and therefore is not limited to the embodiments described herein. In addition, in the drawings, parts that are not related to the description are omitted in order to clearly explain an embodiment of the present specification, and similar parts are designated by similar reference numerals throughout the specification.

[0023] Throughout the specification, when a part is described as being "connected" to another part, this includes not only the case where the part is "directly connected" to another part, but also the case where the part is "indirectly connected" to another part via another member in between. Furthermore, when a part is described as "comprising" a certain component, this does not mean that the part excludes other components, but means that the part can further include other components, unless otherwise specified.

[0024] When a range of numerical values ​​is given herein, unless a specific range is specifically stated, the values ​​have the precision of the significant figures provided in accordance with standard rules in chemistry for significant figures, for example, 10 includes a range of 5.0 to 14.9, and the number 10.0 includes a range of 9.50 to 10.49.

[0025] An embodiment of the present specification will be described in detail below.

[0026] Method for producing latex composition for dip molding A method for producing a dip-molding latex composition according to one embodiment of the present specification includes the steps of: (a) preparing a monomer mixture including a conjugated diene monomer, a farnesene monomer, an ethylenically unsaturated nitrile monomer, and an ethylenically unsaturated acid monomer; (b) adding additives including an emulsifier and an inorganic solvent to the monomer mixture; and (c) polymerizing the monomer mixture to produce a copolymer latex.

[0027] The weight ratio of the farnesene monomer to the total weight of the conjugated diene monomer and the farnesene monomer may be 5 to 55%. For example, the weight ratio of the farnesene monomer to the total weight of the conjugated diene monomer and the farnesene monomer may be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, or a value between any two of these values. If the weight ratio of the farnesene monomer to the total weight of the conjugated diene monomer and the farnesene monomer is less than the above range, the mechanical stability of the latex may decrease, or the stickiness of the final molded product may increase, resulting in decreased durability, and if it exceeds the above range, the latex polymerization reaction rate may decrease, or the gel content of the latex may increase excessively, or the tensile strength and elongation of the final molded product may decrease. For example, if the weight ratio of the farnesene monomer to the total weight of the conjugated diene monomer and the farnesene monomer exceeds the above range, the gel content of the latex may exceed 80%, or the tensile strength and elongation of the final molded product may decrease to less than 90% of the level of a molded product manufactured using a conventional latex composition for dip molding that does not contain a farnesene monomer, and the mechanical properties required for a latex glove may not be satisfied.

[0028] The step (a) is a step of preparing a monomer mixture including a conjugated diene monomer, a farnesene monomer, an ethylenically unsaturated nitrile monomer, and an ethylenically unsaturated acid monomer, which are monomers constituting the copolymer, and may be performed under a nitrogen atmosphere.

[0029] The conjugated diene monomer may be one selected from the group consisting of 1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, isoprene, and a combination of two or more thereof, for example, 1,3-butadiene, but is not limited thereto.

[0030] The content of the conjugated diene monomer may be 40 to 70% by weight based on the total weight of the monomer mixture. For example, it may be 40%, 45%, 50%, 55%, 60%, 65%, 70% by weight, or a value between two of these values. If the content of the conjugated diene monomer is less than the above range, the gel content of the latex may be excessively increased or the tensile strength and elongation of the final molded product may be reduced, and if it exceeds the above range, the mechanical stability of the latex may be reduced or the stickiness of the final molded product may be increased, resulting in reduced durability.

[0031] The farnesene monomer may be an α-farnesene monomer, a β-farnesene monomer, or a combination thereof, such as, but not limited to, a β-farnesene monomer. Farnesene monomers are available from a variety of renewable sources and may be used to prepare environmentally friendly and renewable copolymers. The use of the farnesene monomer can improve the mechanical stability of the latex as well as improve the tackiness and durability of the final molded article.

[0032] The content of the farnesene monomer may be 1 to 39% by weight based on the total weight of the monomer mixture. For example, it may be 1, 5, 10, 15, 20, 25, 30, 35, 39% by weight, or a value between two of these values. If the content of the farnesene monomer is less than the above range, the mechanical stability of the latex may decrease, or the stickiness of the final molded product may increase, decreasing durability, and if it exceeds the above range, the gel content of the latex may increase excessively, or the tensile strength and elongation of the final molded product may decrease.

[0033] The ethylenically unsaturated nitrile monomer may be one selected from the group consisting of acrylonitrile, methacrylonitrile, fumaronitrile, α-chloroacrylonitrile, α-cyanoethylacrylonitrile, and a combination of two or more thereof, for example, acrylonitrile, but is not limited thereto.

[0034] The content of the ethylenically unsaturated nitrile monomer may be 1 to 50% by weight based on the total weight of the monomer mixture. For example, it may be 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50% by weight, or a value between two of these values. If the content of the ethylenically unsaturated nitrile monomer is outside the above range, the molded product may become excessively soft or excessively hardened, resulting in a poor wearing comfort for the user of the dip molded product, or the oil resistance of the dip molded product may decrease, resulting in a low tensile strength.

[0035] The ethylenically unsaturated acid monomer may be one selected from the group consisting of methacrylic acid, acrylic acid, itaconic acid, maleic acid, fumaric acid, maleic anhydride, citraconic anhydride, styrenesulfonic acid, monobutyl fumarate, monobutyl maleate, mono-2-hydroxypropyl maleate, and combinations of two or more thereof, for example, methacrylic acid, but is not limited thereto.

[0036] The content of the ethylenically unsaturated acid monomer may be 1 to 10% by weight based on the total weight of the monomer mixture. For example, it may be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10% by weight, or a value between two of these values. If the content of the ethylenically unsaturated acid monomer is outside the above range, the molded product may become excessively soft or excessively hardened, resulting in poor wearing comfort for the user of the dip molded product, or the oil resistance of the dip molded product may decrease, resulting in low tensile strength.

[0037] The step (b) is a step of preparing emulsion polymerization by adding additives including an emulsifier and an inorganic solvent to the monomer mixture.

[0038] The emulsifier may be, but is not limited to, an ionic surfactant. For example, the emulsifier may be one selected from the group consisting of an anionic surfactant, a cationic surfactant, an amphoteric surfactant, and a combination of two or more thereof.

[0039] The emulsifier may be one selected from the group consisting of alkylbenzenesulfonate, alkyldiphenyloxide disulfonate, aliphatic sulfonate, sulfate of higher alcohol, α-olefinsulfonate, alkyl ether sulfate, and a combination of two or more thereof, for example, sodium alkylbenzenesulfonate, but is not limited thereto.

[0040] The content of the emulsifier may be 0.1 to 5 parts by weight based on 100 parts by weight of the monomer mixture.

[0041] The inorganic solvent may be water, for example, ion-exchanged water, but is not limited thereto.

[0042] The additives may further include a molecular weight regulator.

[0043] The molecular weight regulator may be one selected from the group consisting of mercaptans such as α-methylstyrene dimer, t-dodecyl mercaptan, n-dodecyl mercaptan, octyl mercaptan, etc., halogenated hydrocarbons such as carbon tetrachloride, methylene chloride, methylene bromide, etc., sulfur-containing compounds such as tetraethylthiuram disulfide, dipentamethylenethiuram disulfide, diisopropylxanthogen disulfide, etc., and combinations of two or more of these, for example, t-dodecyl mercaptan, but is not limited thereto.

[0044] The content of the molecular weight regulator may be 0.2 to 0.65 parts by weight based on 100 parts by weight of the monomer mixture. For example, the content of the molecular weight regulator may be 0.2 parts by weight, 0.21 parts by weight, 0.22 parts by weight, 0.23 parts by weight, 0.24 parts by weight, 0.25 parts by weight, 0.26 parts by weight, 0.27 parts by weight, 0.28 parts by weight, 0.29 parts by weight, 0.3 parts by weight, 0.31 parts by weight, 0.32 parts by weight, 0.33 parts by weight, 0.34 parts by weight, 0.35 parts by weight, 0.36 parts by weight, 0.37 parts by weight, 0.38 parts by weight, 0.39 parts by weight, 0.4 parts by weight, 0.41 parts by weight, 0. The content of the molecular weight regulator may be 42 parts by weight, 0.43 parts by weight, 0.44 parts by weight, 0.45 parts by weight, 0.46 parts by weight, 0.47 parts by weight, 0.48 parts by weight, 0.49 parts by weight, 0.5 parts by weight, 0.51 parts by weight, 0.52 parts by weight, 0.53 parts by weight, 0.54 parts by weight, 0.55 parts by weight, 0.56 parts by weight, 0.57 parts by weight, 0.58 parts by weight, 0.59 parts by weight, 0.6 parts by weight, 0.61 parts by weight, 0.62 parts by weight, 0.63 parts by weight, 0.64 parts by weight, 0.65 parts by weight, or a value between two of these values. If the content of the molecular weight regulator is less than the above range, the gel content of the latex may increase, and if it exceeds the above range, the polymerization reaction rate may increase, decreasing the mechanical stability of the latex, or the molecular weight of the latex may decrease, decreasing the tensile strength and durability of the final molded product.

[0045] The step (c) is a step of preparing a copolymer latex by emulsion polymerization of the monomer mixture, and the copolymer latex prepared through the polymerization has a solid content of 30 to 60%, for example, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, or a range between any two of these values. , pH 7 to 12, for example, 7.0, 7.2, 7.4, 7.6, 7.8, 8.0, 8.2, 8.4, 8.6, 8.8, 9.0, 9.2, 9.4, 9.6, 9.8, 10.0, 10.2, 10.4, 10.6, 10.8, 11.0, 11.2, 11.4, 11.6, 11.8, 12.0, or a range between any two of these values, but is not limited thereto.

[0046] The polymerization in step (c) may be carried out at a temperature of 10 to 90°C, for example, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, or a temperature between two of these temperatures.

[0047] The step (c) may include the steps of: polymerizing the monomer mixture by adding a polymerization initiator; terminating the polymerization reaction by adding a polymerization terminator; and removing unreacted monomers and adjusting the solid concentration and pH to obtain a copolymer latex.

[0048] The polymerization initiator may be one selected from the group consisting of inorganic peroxides such as sodium persulfate, potassium persulfate, ammonium persulfate, potassium perphosphate, and hydrogen peroxide, organic peroxides such as t-butyl peroxide, cumene hydroperoxide, p-menthane hydroperoxide, di-t-butyl peroxide, t-butylcumyl peroxide, acetyl peroxide, isobutyl peroxide, octanoyl peroxide, dibenzoyl peroxide, 3,5,5-trimethylhexanoyl peroxide, and t-butylperoxyisobutyrate, azobisisobutyronitrile, azobis-2,4-dimethylvaleronitrile, azobiscyclohexanecarbonitrile, azobisisobutyric acid (butyric acid) methyl, and combinations of two or more of these, for example, potassium peroxodisulfate, but is not limited thereto. The content of the polymerization initiator may be 0.02 to 1.5 parts by weight based on 100 parts by weight of the monomer mixture.

[0049] The polymerization terminator may be added when the conversion rate of the polymerization reaction is 90% or more. For example, the polymerization terminator may be added when the conversion rate of the polymerization reaction is 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.9%, or a value between two of these values.

[0050] The polymerization terminator may be one selected from the group consisting of hydroxylamine, hydroxylamine sulfate, diethylhydroxyamine, hydroxylamine sulfonic acid and its alkali metal ion, sodium hydroxide, sodium dimethyldithiocarbamate, hydroquinone derivatives, aromatic hydroxydithiocarboxylic acids such as hydroxydiethylbenzenedithiocarboxylic acid and hydroxydibutylbenzenedithiocarboxylic acid, and combinations of two or more of these, for example, sodium hydroxide, but is not limited thereto. The content of the polymerization terminator may be 0.02 to 1.5 parts by weight based on 100 parts by weight of the monomer mixture.

[0051] The solids concentration and pH of the copolymer latex may be adjusted by adding additives such as a pH adjuster, an antioxidant, and an antifoaming agent.

[0052] The pH adjuster may be, but is not limited to, an aqueous potassium hydroxide solution or an aqueous ammonia solution.

[0053] The copolymer latex has excellent mechanical stability and may be applied to prepare a stable dip molding latex composition.

[0054] The gel content of the copolymer latex prepared in step (c) may be 80% or less. For example, the gel content of the copolymer latex may be 80% or less, 75% or less, 70% or less, 65% or less, 60% or less, 55% or less, or 50% or less. The gel content of the copolymer latex indicates the degree of cross-linking in the latex. The higher the gel content, the more cross-linking there is. If the gel content of the copolymer latex exceeds the above range, fine cracks or holes may occur in the glove, and the tensile strength and elongation may decrease.

[0055] The method for preparing a latex composition for dip molding may further include the step of (d) adding a vulcanizing agent, a crosslinking agent, and a vulcanization accelerator to the copolymer latex to prepare a latex composition for dip molding.

[0056] The vulcanizing agent may include, but is not limited to, powdered sulfur, precipitated sulfur, colloidal sulfur, surface-treated sulfur, insoluble sulfur, etc. The vulcanizing agent attacks the pi bonds in the conjugated double bonds to crosslink between polymer chains, thereby imparting elasticity to the copolymer and improving the chemical resistance of the dip-molded product. The content of the vulcanizing agent may be 0.1 to 3.0 parts by weight based on 100 parts by weight of the copolymer latex.

[0057] The crosslinking agent may be, but is not limited to, zinc oxide, and the content of the crosslinking agent may be 0.1 to 3.0 parts by weight based on 100 parts by weight of the copolymer latex.

[0058] The vulcanization accelerator may be one selected from the group consisting of 2-mercaptobenzothiazole, 2,2-dithiobisbenzothiozol-2-sulfenamide, N-cyclohexylbenzothiazole-2-sulfenamide, 2-morpholinothiobenzothiazole, tetramethylthiuram monosulfide, tetramethylthiuram disulfide, zinc diethyldithiocarbamate, zinc dibutyldithiocarbamate, diphenylguanidine, di-o-tolylguanidine, and combinations of two or more thereof, for example, zinc dibutyldithiocarbamate, but is not limited thereto. The content of the vulcanization accelerator may be 0.1 to 3.0 parts by weight based on 100 parts by weight of the copolymer latex.

[0059] Latex composition for dip molding The latex composition for dip molding according to another embodiment of the present specification may be produced by the above-mentioned method for producing a latex composition for dip molding, but is not limited thereto.

[0060] The latex composition for dip molding may have a solid content concentration of 10 to 30% by weight and a pH of 9 to 11, but is not limited thereto.

[0061] Dip Molding A dip-molded article according to still another embodiment of the present specification is produced by dip-molding the above-mentioned latex composition for dip molding.

[0062] The dip-molded product has excellent mechanical properties such as tensile strength and elongation, excellent durability, a high coefficient of kinetic friction, little stickiness, and excellent qualities such as texture, and can be used as a dip-molded product in a variety of fields.

[0063] The dip-formed product may be one selected from the group consisting of medical gloves, agricultural and livestock product processing gloves, and industrial gloves, but is not limited thereto.

[0064] The examples of the present specification will be described in more detail below. However, the following experimental results are only representative experimental results among the above examples, and the scope and content of the present specification should not be construed as being narrowed or limited by the examples. The respective effects of various embodiments of the present specification that are not explicitly presented below will be specifically described in the corresponding sections.

[0065] Example 1 A 1L high-pressure reactor equipped with an agitator, a thermometer, a cooler, and a nitrogen gas inlet was prepared so that each component could be continuously added. After the reactor was purged with nitrogen, a monomer mixture containing 57% by weight of 1,3-butadiene, 10% by weight of β-farnesene monomer, 27% by weight of acrylonitrile, and 6% by weight of methacrylic acid based on the total weight of the monomer mixture was added. Then, 0.48 parts by weight of t-dodecyl mercaptan (TDDM) as a molecular weight regulator, 2 parts by weight of sodium alkylbenzene sulfonate as an emulsifier, and 120 parts by weight of ion-exchanged water were added to the reactor based on 100 parts by weight of the monomer mixture. The temperature of the reactor was raised to about 30° C., and 0.3 parts by weight of potassium persulfate as a polymerization initiator was added.

[0066] When the conversion rate based on the monomer mixture reached about 95%, 0.9 parts by weight of sodium hydroxide was added to terminate the polymerization reaction. Thereafter, unreacted monomers were removed through a deodorization process, and ammonia water, an antioxidant, an antifoaming agent, etc. were added to obtain a carboxylic acid-modified nitrile copolymer latex with a solid content concentration of 45% by weight and a pH of 8.5.

[0067] Example 2 A carboxylic acid modified nitrile copolymer latex was obtained in the same manner as in Example 1, except that a monomer mixture containing 52% by weight of 1,3-butadiene and 15% by weight of β-farnesene monomer was added, and 0.52 parts by weight of t-dodecyl mercaptan was added.

[0068] Example 3 A carboxylic acid modified nitrile copolymer latex was obtained in the same manner as in Example 1, except that a monomer mixture containing 47% by weight of 1,3-butadiene and 20% by weight of β-farnesene monomer was added, and 0.60 parts by weight of t-dodecyl mercaptan was added.

[0069] Example 4 A carboxylic acid modified nitrile copolymer latex was obtained in the same manner as in Example 1, except that a monomer mixture containing 37% by weight of 1,3-butadiene and 30% by weight of β-farnesene monomer was added, and 0.64 parts by weight of t-dodecyl mercaptan was added.

[0070] Comparative Example 1 A carboxylic acid modified nitrile copolymer latex was obtained in the same manner as in Example 1, except that a monomer mixture containing no β-farnesene monomer and having a 1,3-butadiene content of 67 wt % was used.

[0071] Comparative Example 2 A carboxylic acid modified nitrile copolymer latex was obtained in the same manner as in Example 1, except that a monomer mixture containing 27% by weight of 1,3-butadiene and 40% by weight of β-farnesene monomer was used.

[0072] Comparative Example 3 A carboxylic acid modified nitrile copolymer latex was obtained in the same manner as in Example 1, except that a monomer mixture containing no 1,3-butadiene and 67% by weight of β-farnesene monomer was used.

[0073] Comparative Example 4 A carboxylic acid-modified nitrile copolymer latex was obtained in the same manner as in Comparative Example 1, except that 0.64 parts by weight of t-dodecyl mercaptan was added.

[0074] Comparative Example 5 A carboxylic acid-modified nitrile copolymer latex was obtained in the same manner as in Example 1, except that 0.68 parts by weight of t-dodecyl mercaptan was added.

[0075] Comparative Example 6 A carboxylic acid-modified nitrile copolymer latex was obtained in the same manner as in Example 3, except that 0.72 parts by weight of t-dodecyl mercaptan was added.

[0076] Comparative Example 7 A carboxylic acid-modified nitrile copolymer latex was obtained in the same manner as in Example 4, except that 0.76 parts by weight of t-dodecyl mercaptan was added.

[0077] Table 1 below shows the 1,3-butadiene content, β-farnesene monomer content, weight ratio of β-farnesene monomer to the total weight of 1,3-butadiene and β-farnesene monomer, and content of t-dodecyl mercaptan as a molecular weight regulator in the monomer mixtures used in polymerization of the carboxylic acid modified nitrile copolymer latexes of Examples 1 to 4 and Comparative Examples 1 to 7.

[0078] [Table 1]

[0079] Experimental Example 1 Experimental Example 1-1: Evaluation of mechanical stability A latex stability test (Maron test) was conducted to evaluate the mechanical stability of each of the carboxylic acid modified nitrile copolymer latexes prepared in Examples 1 to 4 and Comparative Examples 1 to 7. The latex stability test was conducted using a Maron tester, in which 30 g of a latex sample was placed in a sample frame, and a shear stress of 49 N and 1000 rpm was applied for 1 minute, after which the weight of the aggregates generated was measured. The lower the weight of the aggregates generated during the latex stability test, the more excellent the mechanical stability is.

[0080] Experimental Example 1-2: Measurement of gel content 5 g of each of the carboxylic acid-modified nitrile copolymer latexes prepared in Examples 1 to 4 and Comparative Examples 1 to 7 was added to 200 mL of isopropyl alcohol under stirring to coagulate. The coagulated material was filtered through a 120 mesh wire screen, dried in a thermostatic vacuum dryer at 50±2°C and 750±10 mmHg for 1 hour, and then left to stand in a desiccator until it reached room temperature. The basis weight (W) of 0.25 to 0.35 g of the dried sample was measured accurately to an accuracy of 0.1 mg. i ) and placed in an Erlenmeyer flask, 100 mL of methyl ethyl ketone (MEK) was added, and the mixture was stirred for 2 hours. The entire sample was then filtered through filter paper. 20 mL of the filtrate was heated to evaporate the methyl ethyl ketone, and then cooled to room temperature in a desiccator. The basis weight (W f The gel content in the sample was measured using the following formula 1, and the average of the two values ​​was calculated to one decimal place.

[0081]

number

[0082] The following Table 2 shows the mechanical stability evaluation and gel content measurement results for each of the carboxylic acid-modified nitrile copolymer latexes produced in Examples 1 to 4 and Comparative Examples 1 to 7.

[0083] [Table 2]

[0084] Referring to Table 2, the carboxylic acid modified nitrile copolymer latexes of Examples 1 to 4, in which the weight ratio of β-farnesene monomer to the total weight of 1,3-butadiene and β-farnesene monomer used in polymerization was 15%, 22%, 30%, and 45%, respectively, and the content of t-dodecyl mercaptan as a molecular weight modifier was 0.48 to 0.64 parts by weight based on 100 parts by weight of the monomer mixture, showed superior mechanical stability compared to Comparative Examples 1 and 4, which did not use β-farnesene monomer, and Comparative Examples 5 to 7, in which 0.68 to 0.76 parts by weight of a molecular weight modifier was added.

[0085] In addition, the gel contents of the carboxylic acid modified nitrile copolymer latexes of Examples 1 to 4 were all excellent values ​​of 80% or less, but it was confirmed that the gel contents of the carboxylic acid modified nitrile copolymer latexes of Comparative Examples 2 and 3, in which the weight ratios of β-farnesene monomer to the total weight of 1,3-butadiene and β-farnesene monomer used in polymerization were 60% and 100%, respectively, exceeded 80%.

[0086] Manufacturing Example To 100 parts by weight of each of the carboxylic acid modified nitrile copolymer latexes prepared in Examples 1 to 4 and Comparative Examples 1 to 7, 1.0 part by weight of sulfur, 1.2 parts by weight of zinc oxide, and 0.5 parts by weight of zinc dibutyldithiocarbamate (ZDBC) as a vulcanization accelerator were added, and a 4% aqueous potassium hydroxide solution and secondary distilled water were added to prepare a dip molding latex composition having a solid content of 18% and a pH of 10.0.

[0087] Experimental Example 2 Experimental Example 2-1: Evaluation of mechanical properties From each of the dip molding latex compositions produced in the above-mentioned production examples, dumbbell-shaped test pieces were prepared according to ASTM D-412. The test pieces were pulled at an elongation rate of 500 mm / min using a UTM (Universal Testing Machine), and the tensile strength and elongation at break were measured to evaluate the mechanical properties. Generally, the higher the tensile strength and elongation of a latex molded product, the better the dip quality is evaluated to be.

[0088] Experimental Example 2-2: Measurement of the coefficient of kinetic friction After preparing a film test piece of each of the dip molding latex compositions produced according to the above production examples, the friction coefficient of the latex side of the test piece (the part that touches the hand during glove production) was measured using a friction coefficient measuring device. The sled size of the friction coefficient measuring device was set to 30 mm, and the vertical load was set to 100 g. After placing a sled on the test piece of the dip molding latex composition, the kinetic friction coefficient value was measured from the average value of the load values ​​read while the sled on the upper surface of the film moved while pulling 50 mm. It can be evaluated that the lower the kinetic friction coefficient value, the more improved the stickiness of the dip molded product.

[0089] Experimental Example 2-3: Evaluation of durability A test piece having a width of 30 mm, a length of 135 mm, and a thickness of 0.06 to 0.08 mm was prepared from each of the dip molding latex compositions prepared according to the above Preparation Examples. The dip molded product was immersed in a citric acid solution of pH 4.0 to 4.3 at 35°C in a state of being stretched by 20% in the longitudinal direction and fixed with a clamp, and the process of stretching the product by using a motor so that the longitudinal elongation rate becomes 50% for 10 seconds, fixing it for 2 seconds, and then relaxing the product by the longitudinal elongation rate becomes 20% for 10 seconds was repeated, and the time until the test piece broke was measured up to a maximum of 180 minutes.

[0090] The following Table 3 shows the results of evaluation of mechanical properties, measurement of kinetic friction coefficient, and evaluation of durability of test pieces prepared from each of the dip molding latex compositions prepared in the above Preparation Examples.

[0091] [Table 3]

[0092] Referring to Table 3, the carboxylic acid modified nitrile copolymer latexes of Examples 1 to 4, in which the weight ratio of β-farnesene monomer to the total weight of 1,3-butadiene and β-farnesene monomer used in polymerization is 15%, 22%, 30%, and 45%, respectively, and the content of t-dodecyl mercaptan, a molecular weight modifier, is 0.48 to 0.64 parts by weight based on 100 parts by weight of the monomer mixture, exhibit a similar level of tensile strength to the conventional carboxylic acid modified nitrile copolymer latexes of Comparative Examples 1 and 4, in which β-farnesene monomer is not used, and satisfy the mechanical properties required for latex gloves. Meanwhile, the tensile strengths of the carboxylic acid modified nitrile copolymer latexes of Comparative Examples 2 and 3, in which the weight ratio of β-farnesene monomer is 60% and 100%, respectively, and the carboxylic acid modified nitrile copolymer latexes of Comparative Examples 5 to 7, in which 0.68 to 0.76 parts by weight of a molecular weight modifier is added, are less than 90% of the tensile strength of the carboxylic acid modified nitrile copolymer latexes of Comparative Example 1 or Comparative Example 4, in which no β-farnesene monomer is used, and it was confirmed that the mechanical properties are deteriorated.

[0093] In addition, the elongation of the carboxylic acid modified nitrile copolymer latexes of Examples 1 to 4, in which the weight ratio of β-farnesene monomer is 15%, 22%, 30%, and 45% relative to the total weight of 1,3-butadiene and β-farnesene monomer used in polymerization, respectively, was similar to that of the conventional carboxylic acid modified nitrile copolymer latexes of Comparative Examples 1 and 4, in which β-farnesene monomer was not used, and thus the mechanical properties required for latex gloves were satisfied. On the other hand, the elongation of the carboxylic acid modified nitrile copolymer latexes of Comparative Examples 2 and 3, in which the weight ratio of β-farnesene monomer is 60% and 100%, respectively, was less than 90% of that of the carboxylic acid modified nitrile copolymer latex of Comparative Example 1, in which β-farnesene monomer was not used, and thus it was confirmed that the mechanical properties were deteriorated.

[0094] In terms of the kinetic friction coefficient and durability, the carboxylic acid modified nitrile copolymer latexes of Examples 1 to 4 using β-farnesene monomer showed superior values ​​compared to the carboxylic acid modified nitrile copolymer latex of Comparative Example 1 using no β-farnesene monomer.

[0095] The above description of the present specification is for illustrative purposes only, and a person having ordinary skill in the art to which one embodiment of the present specification belongs can easily understand that the present specification can be easily modified into other specific forms without changing the technical ideas and essential features described in the present specification. Therefore, it should be understood that the above-described embodiments are illustrative in all respects and are not limiting. For example, each component described in a single form may be implemented in a distributed form, and similarly, each component described as being distributed may be implemented in a combined form.

[0096] The scope of this specification is defined by the claims set forth below, and all modifications and variations derived from the meaning and scope of the claims and their equivalent concepts should be construed as being included in the scope of this specification.

Claims

1. (a) providing a monomer mixture comprising a conjugated diene monomer, a farnesene monomer, an ethylenically unsaturated nitrile monomer, and an ethylenically unsaturated acid monomer; (b) adding additives including an emulsifier, an inorganic solvent, and a molecular weight regulator to the monomer mixture; (c) polymerizing the monomer mixture to produce a copolymer latex; a weight ratio of the farnesene monomer to the total weight of the conjugated diene monomer and the farnesene monomer is 5 to 55%; The content of the molecular weight regulator is 0.2 to 0.65 parts by weight based on 100 parts by weight of the monomer mixture. A method for producing a latex composition for dip molding.

2. The method for producing a dip-molding latex composition according to claim 1, wherein the conjugated diene monomer is one selected from the group consisting of 1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, isoprene, and a combination of two or more thereof.

3. 2. The method for producing a dip-molding latex composition according to claim 1, wherein the farnesene monomer is an α-farnesene monomer, a β-farnesene monomer, or a combination thereof.

4. The method for producing a dip-molding latex composition according to claim 1, wherein the ethylenically unsaturated nitrile monomer is one selected from the group consisting of acrylonitrile, methacrylonitrile, fumaronitrile, α-chloroacrylonitrile, α-cyanoethylacrylonitrile, and a combination of two or more thereof.

5. The method for producing a dip-molding latex composition according to claim 1, wherein the ethylenically unsaturated acid monomer is one selected from the group consisting of methacrylic acid, acrylic acid, itaconic acid, maleic acid, fumaric acid, maleic anhydride, citraconic anhydride, styrenesulfonic acid, monobutyl fumarate, monobutyl maleate, mono-2-hydroxypropyl maleate, and a combination of two or more thereof.

6. 2. The method for producing a dip-molding latex composition according to claim 1, wherein the molecular weight regulator is one selected from the group consisting of α-methylstyrene dimer, mercaptans, halogenated hydrocarbons, sulfur-containing compounds, and combinations of two or more thereof.

7. The method for producing a latex composition for dip molding according to claim 1, wherein the molecular weight regulator is one selected from the group consisting of α-methylstyrene dimer, t-dodecyl mercaptan, n-dodecyl mercaptan, octyl mercaptan, carbon tetrachloride, methylene chloride, methylene bromide, tetraethylthiuram disulfide, dipentamethylene thiuram disulfide, diisopropylxanthogen disulfide, and combinations of two or more thereof.

8. 2. The method of claim 1, wherein the copolymer latex prepared in step (c) has a gel content of 80% or less.

9. A method for producing a dip-molded product, comprising: producing a latex composition for dip molding by the method according to any one of claims 1 to 8; and dip molding the latex composition for dip molding.

10. The method for producing a dip-molded product according to claim 9, wherein the dip-molded product is one selected from the group consisting of medical gloves, agricultural and livestock product processing gloves, and industrial gloves.

Citation Information

Patent Citations

  • Polymerization of compositions containing farnesene

    JP2015511266A

  • Latex composition for dip molding, its manufacturing method, and dip-molded article manufactured using the same

    JP2022511011A

  • How to repair or recycle elastomer film

    JP2022533361A

  • Polymer latex compositions for the preparation of elastomeric films with self-healing properties - Patent Application 20070122997

    JP2022551795A

  • Aqueous emulsion, thin molded article, and method for producing thin molded article

    WO2015119248A1